Power Distance between Teacher and Students in Learning Process Based on Curriculum 2013 (Case Study: SDN Babakan 02, Setu, Tangerang Selatan) - Vusparatih, Dina Sekar (Bina Nusantara University, 2017)
This study talked the high power distance level between teachers and students in Indonesian society, especially in public schools. Creating two-way communication in intercultural communication that had high power distance will be a big challenge for teachers. This study used the qualitative method and the case study in of SDN Babakan 02, Setu, South Tangerang. It would see how the teacher's efforts in reducing the power distance that was in the learning process when the implementation of Curriculum 2013. Using in-depth interview and observation technique, all data needed was collected. In the end, this research has captured that teachers still need to know more about the Curriculum 2013. To share power distance as part of the curriculum is still difficult since the teachers do not have same understanding and perspective about K13.